Analysis of aerodynamic simulation of air flow modes with nasal breathing disorders - Ibrahim Younouss Abdelhamid; Аврунін, О. Г. (ХНУРЕ, 2018)
There is studing the most important aerodynamic processes occurring in the nasal airway specifically with breathing disorders, and to identify the most important respiratory functions of the upper respiratory system
Keywords: Nasal aerodynamics; air passageway